2021
DOI: 10.3311/ppci.17016
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Performance of Alkali Activated Concretes under Different Curing Conditions

Abstract: This study investigated the influence of different curing conditions on the compressive strength (CS) of the different alkali activated concrete (AAC) specimens at the ages of 2, 28, and 90 days for the structural utilization and standardization process of AAC instead of OPC concrete. For this aim, 100% slag (S100), 75% slag and 25% fly ash (S75FA25), and 50% slag and 50% fly ash based (S50FA50) AAC specimens were produced. Based on the oven-curing (O), water-curing (W), and ambient-curing (A) methods, the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For the workability enhancement and further geopolymerization, additional water is also utilized in the mixes. 26…”
Section: Methodsmentioning
confidence: 99%
“…For the workability enhancement and further geopolymerization, additional water is also utilized in the mixes. 26…”
Section: Methodsmentioning
confidence: 99%
“…The produced rubberized samples were demolded after 24 h later and then kept in the laboratory medium at 23 ± 2•C at the ages of 28 days. In the previous investigation, it was reported that slag-based alkali activated concretes can be utilized in structural applications without oven-curing or water curing [22]. Therefore, oven-curing or water curing was not applied to the specimens.…”
Section: Curing Methods Of the Rubberized Scaac Samplesmentioning
confidence: 99%
“…For low calcium-based systems, water curing could cause material strength reduction and alkaline cation leaching [66]. In high-calcium-based systems, water immersion can have the opposite effect, resulting in high compressive strength [67] and lower permeability [68]. The difference is mainly caused by the rapid formation of the silica-rich matrix, including calcium silicate hydrate (C-S-H) in the pore space within high calcium mixtures through water consumption, which contributes to the early strength formation [69][70][71].…”
Section: Curing Conditionsmentioning
confidence: 99%